Pig inspection: software for the visual inspection system in pigs - Passos Pequeno, Andréia (2020)
One of the main purposes of meat inspection is to prevent and detect public health hazards, such as foodborne pathogens or chemical contaminants in meat. Furthermore, the information obtained from slaughter animals allows for the planning of animal health management programmes and monitoring the effectiveness of disease treatment and prevention strategies (1, 2). There is a consensus in recognizing that traditional meat inspection is no longer able to address the hazards related to meat consumption. For these reasons, legislations all over the world are changing meat inspection techniques, moving towards visual-only techniques. The visual-only inspection has showed greater efficiency than the traditional inspection in detecting lesions. However, many countries still do not have data on possible applications of a visual inspection system in pigs, moreover consistent data on post-mortem lesions for pigs in the slaughterhouse is missing. There is also great difficulty in the criteria for condemnation of organs or carcass (4, 5). Therefore, the objective of the present study was to develop a software designed to recognize, classify and quantify the main diseases and macroscopic lesions that attack the pigs of age to slaughter in the post-mortem inspection stage.